FDG PET/CT negative medullary thyroid carcinoma patient with elevated CEA level: Case report and review of literature - Koç, Zehra Pınar; Uğur Aksoy, Kader; Keleş, Erol; Dağli, Ferda; Narin, Yavuz (Turkiye Klinikleri, 2017)
The tumor markers are considered reliable in follow up of Medullary Thyroid carcinoma (MTC) as an adjunct with other imaging methods like ultrasonography. In some circumstances imaging of thorax or whole body imaging may be necessary in these patients in the follow up. Calcitonin levels in combination with carcinoembryonic antigen is markers that we use in the follow up of MTC patients which elevation indicates recurrence and the recurrence cite may be described by means of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (F-18 FDG PET/CT) imaging which was negative in our case. In this case we report a patient with exceptionally high carcinoembryonic antigen (CEA) and low calcitonin level in one month postoperative follow up who was diagnosed as having false positive CEA elevation and discuss the diagnostic methods and tumor markers in detection of the Medullary Thyroid carcinoma. © 2017 by Türkiye Klinikleri.
FDG PET/BT Negatif Yükselmiş CEA Değerleri Olan Medüller Tiroid Karsinomu Hastası: Olgu Sunumu ve Literatür Derlemesi
Keywords: Calcitonin; Carcinoembryonic antigen; Fluorodeoxyglucose F18; Medullary; Positron-emission tomography; Thyroid cancer